Hubungan Antara Habits of Mind dengan Kemampuan Berpikir Kritis Matematis Siswa Kelas IX SMPN 1 Montong Gading Tahun Ajaran 2024/2025 - Muniro, Nisrina; Syahrul Azmi; Nilza Humaira Salsabila; Nani Kurniati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
Mathematical critical thinking skills are critical thinking skills that involve cognitive processes and encourage students to think reflectively which are developed in mathematics learning. Mathematical critical thinking skill is necessary for students in solving mathematical problems. However, in reality, many students have low critical mathematical thinking skills. Several researchers have studied there is correlation between mathematical critical thinking skill to students habits of mind. Therefore, this research aims to determine the correlation between habits of mind and critical mathematical thinking abilities of class IX students at SMP Negeri 1 Montong Gading. This research is a non-experimental descriptive quantitative research with a correlation method. Sampling method used purposive sampling technique to obtain data from class IX B students of SMPN 1 Montong Gading with a total of 26 students as samples. Data collection techniques include giving habits of mind questionnaires, testing students' critical mathematical thinking skills and interviews. This research uses descriptive techniques and prerequisite tests. The research results show that habits of mind and mathematical critical thinking skills are included in the medium category with percentages of 65% and 62%. The results of the correlation analysis using the pearson product moment formula show that there is a significant relationship between habits of mind and students' mathematical critical thinking abilities with a correlation value of 0.481946, which is categorized as a medium level correlation. Keywords: Habits of mind, mathematical critical thinking